Development and validation of a GCâFID method for quantitative analysis of oleic acid and related fatty acids - Honggen Zhang; Zhenyu Wang; Oscar Liu (Elsevier, 2015)
Oleic acid is a common pharmaceutical excipient that has been widely used in various dosage forms. Gas chromatography (GC) has often been used as the quantitation method for fatty acids normally requiring a derivatization step. The aim of this study was to develop a simple, robust, and derivatization-free GC method that is suitable for routine analysis of all the major components in oleic acid USP-NF (United States Pharmacopeia-National Formulary) material. A gas chromatographyâflame ionization detection (GCâFID) method was developed for direct quantitative analysis of oleic acid and related fatty acids in oleic acid USP-NF material. Fifteen fatty acids were separated using a DB-FFAP (nitroterephthalic acid modified polyethylene glycol) capillary GC column (30Â mÃ0.32Â mm i.d.) with a total run time of 20Â min. The method was validated in terms of specificity, linearity, precision, accuracy, sensitivity, and robustness. The method can be routinely used for the purpose of oleic acid USP-NF material analysis. Keywords: Oleic acid, Fatty acids, Gas chromatography, Method development, Derivatization-free